Functional and evolutionary analyses of the miR156 and miR529 families in land plants - Morea, Edna Gicela Ortiz [UNESP] (2016)
Background: MicroRNAs (miRNAs) are important regulatory elements of gene expression. Similarly to coding genes, miRNA genes follow a birth and death pattern of evolution likely reflecting functional relevance and divergence. For instance, miRNA529 is evolutionarily related to miRNA156 (a highly conserved miRNA in land plants), but it is lost in Arabidopsis thaliana. Interestingly, both miRNAs target sequences overlap in some members of the SQUAMOSA promoter-binding protein like (SPL) family, raising important questions regarding the diversification of the miR156/miR529-associated regulatory network in land plants. Results: In this study, through phylogenic reconstruction of miR156/529 target sequences from several taxonomic groups, we have found that specific eudicot SPLs, despite miRNA529 loss, retained the corresponding target site. Detailed molecular evolutionary analyses of miR156/miR529-target sequence showed that loss of miR529 in core eudicots, such as Arabidopsis, is correlated with a more relaxed selection of the miRNA529 specific target element, while miRNA156-specific target sequence is under stronger selection, indicating that these two target sites might be under distinct evolutionary constraints. Importantly, over-expression in Arabidopsis of MIR529 precursor from a monocot, but not from a basal eudicot, demonstrates specific miR529 regulation of AtSPL9 and AtSPL15 genes, which contain conserved responsive elements for both miR156 and miR529. Conclusions: Our results suggest loss of functionality of MIR529 genes in the evolutionary history of eudicots and show that the miR529-responsive element present in some eudicot SPLs is still functional. Our data support the notion that particular miRNA156 family members might have compensated for the loss of miR529 regulation in eudicot species, which concomitantly may have favored diversification of eudicot SPLs.